FUZZY LIE IDEALS OVER A FUZZY FIELD - Akram, M.; Shum, K.P. (Italian Journal of Pure and Applied Mathematics, 2010)
The concept of fuzzy Lie ideals of a Lie algebra over a fuzzy field is introduced and some fundamental properties of such fuzzy Lie ideals are given. We then characterize the Artinian and Noetherian Lie algebras by considering their fuzzy Lie ideals over a fuzzy field.